Formula Apportionment in the European Union: A Dream Come True or the EU's Worst Nightmare? - Joann Weiner (Center for Economic Studies and ifo Institute (CESifo), 2002)
The European Commission recently endorsed a future company tax policy that would allow companies to consolidate their tax bases and apportion the income across the EU using an allocation mechanism. This policy would replace the separate accounting method with formula apportionment of EU group profits as the main method of taxing multinational companies in the European Union. However, many details of the approaches remain to be presented, and these details may turn what appears to be a simple solution into an extremely complex one. This paper explores some technical details that arise in adopting formula apportionment in the European Union.
Keywords: 330